Village policy study in overcoming social and economic inequality in local communities - Massenga, Talitha Wenifrida (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Social and economic inequalities in local communities are significant challenges in achieving sustainable development, particularly in rural areas. This study aims to evaluate village policies designed to address these inequalities at the local level. A qualitative approach, combining document analysis, in-depth interviews, and field observations, was used to collect data from village development reports, policy documents, and interviews with village officials, community leaders, and residents in several regions of Indonesia, including Central Java, West Sumatra, and South Sulawesi. The data were analyzed using content analysis to assess the effectiveness of these policies and their impact on reducing inequality. The study finds that village policies such as the allocation of Village Funds (DD), community-based economic empowerment initiatives, and social protection programs have played a crucial role in alleviating social and economic disparities. For example, the implementation of the Village Fund has facilitated improvements in infrastructure, including the construction of roads, access to clean water, and educational facilities, directly enhancing the community’s quality of life. Moreover, community-driven economic programs, such as the establishment of Village-Owned Enterprises (BUMDes), have led to job creation and increased household incomes. However, the study also identifies significant challenges, including limited governance capacity at the village level, insufficient community participation, and weak supervision of policy implementation. This research concludes that while village policies have the potential to reduce inequality, their success depends on good governance, increased community involvement, and stronger oversight mechanisms. Concrete recommendations include enhancing the capacity of village governments through training in financial management and project planning, utilizing digital technology for transparent budgeting, and integrating village policies more effectively with national development programs to ensure sustainable outcomes.